2007
DOI: 10.1007/s00011-007-7023-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of acute visceral nociception and bladder inflammation by plant triterpene, α, β-amyrin in a mouse model of cystitis: role of tachykinin NK1-receptors, and K+ ATP channels

Abstract: alpha, beta-amyrin attenuates CPM-induced visceral pain and bladder edema by mechanisms that involve, at least in part, a block either of Substance P release or its receptor function, and partly by opening K(+) (ATP) channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Later, this model was validated in mice by several research groups as a useful experimental approach for evaluating inflammatory and visceral nociceptive changes associated to CYP (Olivar and Laird 1999;Lima-Junior et al 2007;Wantuch et al 2007;Tripathi and Jena 2009). Our study revealed the beneficial effects for P. niruri extract and the isolated compounds quercetin, gallic acid, and rutin in preventing the inflammatory and nociceptive alterations evoked by CYP administration in mice, when compared with those seen with Mesna.…”
Section: Discussionmentioning
confidence: 55%
“…Later, this model was validated in mice by several research groups as a useful experimental approach for evaluating inflammatory and visceral nociceptive changes associated to CYP (Olivar and Laird 1999;Lima-Junior et al 2007;Wantuch et al 2007;Tripathi and Jena 2009). Our study revealed the beneficial effects for P. niruri extract and the isolated compounds quercetin, gallic acid, and rutin in preventing the inflammatory and nociceptive alterations evoked by CYP administration in mice, when compared with those seen with Mesna.…”
Section: Discussionmentioning
confidence: 55%
“…In this context, our previous studies demonstrated the antinociceptive effects of a,b-amyrin in experimental models of nociception induced by capsaicin (TRPV1 agonist) [20,45] and in visceral nociception induced by ciclophosphamide, by mechanisms that involve, at least in part, tachykinin NK(1)-receptors and K(? )(ATP) channels [22]. Future studies should examine the efficacy of a,bamyrin in mitigating pancreatic pain in animal models of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The major component of the resin is a,b-amyrin, a pentacyclic triterpene, and our previous studies established its antiinflammatory, antipruritic, gastroprotective, and hepatoprotective activities [17][18][19][20]. A few other studies reported on its suppressive effect on acute visceral and orofacial nociception and bladder inflammation in a mouse model of cystitis [21][22][23]. Since these studies established the anti-inflammatory, antinociceptive, and antioxidant properties of a,b-amyrin, the present study evaluated its potential to ameliorate pancreatic injury in a ceruleininduced murine model of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…These triterpenes have been reported to exert anti-inflammatory properties in various animal models, including colitis, cystitis or pancreatitis. [7][8][9] In the central nervous system, α-and β-amyrin have been reported to exhibit anti-nociceptive properties via the activation of cannabinoid receptors 10,11) and to exhibit antianxiety or anti-depression properties through the modulation of the benzodiazepine site of the γ-aminobutyric acid type A (GABA A ) receptor or noradrenergic receptor, respectively.…”
mentioning
confidence: 99%